Women in hotel management in Zimbabwe: career ambitions, progression tactics, and career challenges - Mkono, Muchazondida (University of the Aegean, 2021)
Research investigates career ambitions, progression tactics and challenges among female hotel managers in Zimbabwean hotels. Data was gathered through a questionnaire survey of 84 female hotel managers in Zimbabwe. Most female hotel managers in Zimbabwe aspire to attain top management positions. However, they face several challenges in their attempts to achieve their career goals. To enhance their career progression prospects, there is a clear need to adopt more aggressive tactics, especially with regard to undertaking further study. For the industry there is need to institutionalise policies and structures that are more "woman-friendly". However, cultural norms and values pose a major challenge for the change process. Further, women should take responsibility for their own careers. They could strengthen their promotion chances by undertaking postgraduate business leadership courses at esteemed institutions, and by being more assertive of their capabilities. The research focuses on Zimbabwean female hotel managers, whose career ambitions, progression tactics and challenges have not yet been documented.